Logo design love : a guide to creating iconic brand identities. - Airey, David, ....- (Berkeley : New Riders, 2010)
There are a lot of books out there that show collections of logos. But David Airey's Logo Design Love is something different: it's a guide for designers (and clients) who want to understand what this mysterious business is all about. Written in reader-friendly, concise language, with a minimum of designer jargon, Airey gives a surprisingly clear explanation of the process, using a wide assortment of real-life examples to support his points. Anyone involved in creating visual identities, or wanting to learn how to go about it, will find this book invaluable. - Tom Geismar, Chermayeff & Geismar In Logo Design Love, Irish graphic designer David Airey brings the best parts of his wildly popular blog of the same name to the printed page. Just as in the blog, David fills each page of this simple, modern-looking book with gorgeous logos and real world anecdotes that illustrate best practices for designing brand identity systems that last. David not only shares his experiences working with clients, including sketches and final results of his successful designs, but uses the work of many well-known designers to explain why well-crafted brand identity systems are important, how to create iconic logos, and how to best work with clients to achieve success as a designer. Contributors include Gerard Huerta, who designed the logos for Timemagazine and Waldenbooks; Lindon Leader, who created the current FedEx brand identity system as well as the CIGNA logo; and many more. Readers will learn: Why one logo is more effective than another How to create their own iconic designs What sets some designers above the rest Best practices for working with clients 25 practical design tips for creating logos that last